KINEMATICS ANALYSIS OF HIGH-SPEED ANGULAR CONTACT BALL BEARINGS BASED ON FINITE ELEMENT - BIAN Qiang; ZENG Guang; ZHAO ChunJiang; LIU BingYang; XIAO ZhiGang (Jixie qiangdu)
Because the traditional method is not easy to test the motion characteristics of angular contact ball bearings under high-speed operation,a multi-body dynamic finite element model of balls,cages and rings was established based on ABAQUS.Taking 7005 type angular contact ball bearings as the research object,the variation of the linear velocity of the ball and the sliding rate of the cage under different axial load,radial load and rotation speed were studied. The study found that when the axial load increases,the amplitude of the linear velocity fluctuation of the ball gradually decreases,and the sliding rate of the cage gradually decreases. With the radial load increases,the fluctuation of the ball linear velocity amplitude gradually increases,and the sliding rate of the cage increases. When the rotation speed increases,the fluctuation of the ball linear velocity amplitude gradually increases,and the sliding rate of the cage also gradually increases. The finite element simulation results are compared with the theoretical values to verify that the finite element calculation results are closer to the actual working conditions.